Ulnar Shortening Osteotomy for Distal Radius Malunion - Kamal, Robin N. (Thieme Medical Publishers, 2014)
Background Malunion is a common complication of distal radius fractures. Ulnar shortening osteotomy (USO) may be an effective treatment for distal radius malunion when appropriate indications are observed. Methods The use of USO for treatment of distal radius fracture malunion is described for older patients (typically patients >50 years) with dorsal or volar tilt less than 20 degrees and no carpal malalignment or intercarpal or distal radioulnar joint (DRUJ) arthritis. Description of Technique Preoperative radiographs are examined to ensure there are no contraindications to ulnar shortening osteotomy. The neutral posteroanterior (PA) radiograph is used to measure ulnar variance and to estimate the amount of ulnar shortening required. An ulnar, mid-sagittal incision is used and the dorsal sensory branch of the ulnar nerve is preserved. An USO-specific plating system with cutting jig is used to create parallel oblique osteotomies to facilitate shortening. Intraoperative fluoroscopy and clinical range of motion are checked to ensure adequate shortening and congruous reduction of the ulnar head within the sigmoid notch. Results Previous outcomes evaluation of USO has demonstrated improvement in functional activities, including average flexion-extension and pronosupination motions, and patient reported outcomes. Conclusion The concept and technique of USO are reviewed for the treatment of distal radius malunion when specific indications are observed. Careful attention to detail related to surgical indications and to surgical technique typically will improve range of motion, pain scores, and patient-reported outcomes and will reduce the inherent risks of the procedure, such as ulnar nonunion or the symptoms related to unrecognized joint arthritis. Level of Evidence: Level IV